Effect of Alternating Stray Current Density on Corrosion Behavior of X80 Steel under Disbonded Coating. (28th June 2021) - Ding, Qing-Miao; Qin, Yong-Xiang; Shen, Tao; Gao, Yu-ning
Abstract : In this paper, the effect of alternating stray current (AC) density on the corrosion behavior of X80 steel under disbonded coating was studied by electrochemical methods, wire beam electrode (WBE) technology, and surface observation technology. The results showed that under the interference of different AC densities, the corrosion potential of X80 steel under disbonded coating underwent negative deviation, and the degree of negative deviation increased with the increase of AC density. The corrosion current density of X80 steel under disbonded coating with the action of 0 100 A/m 2 AC density had few differences. While the corrosion current density of X80 steel with the action of 200 300 A/m 2 AC density increased and the corrosion current density was higher than that under low AC density. The cathode area of the wire beam electrode under disbonded coating is mainly distributed outside and the edge of the gap between disbonded coating and X80 steel, while the anode area is mainly distributed inside the gap.